Review dan Analisis Degister Tank dengan fluida POME Berdasarkan API 650 Menggunakan Variable Design Point Method - Hana Hermawan; Winda Wulandari (Badan Kerja Sama Teknik Mesin Indonesia, 2020)
POME is a by-product of palm oil production with a ratio contained in palm oil of 58.3%. POME can be used as biogas with anaerobic processing technology using a Continuous Stirred Tank Reactor (CSTR). The purpose of this study is to review and analyze the digester tank with POME fluid based on the American Petroleum Institute standard, API 650: Welded Steel Tanks for Oil Storage using a variable design point method to determine the minimum thickness of each shell depending on its depth, so that each shell can have different thickness so as to reduce the volume of material and cost. Then simulations are performed with the finite element method with a load of hydrostatic pressure that produces a maximum stress of 154.88 MPa, and a maximum deformation of 5 mm and a load of wind force that produces a maximum stress of 1.31 MPa, and a maximum deformation 0.5 mm, then compared with the mechanical properties of the material that yield strength occurs at a voltage of 250-395 MPa so that the thickness of the calculated shell is safe. Then compare the minimum thickness calculation results with the construction design which results are the construction design has a thickness that is greater than the minimum thickness calculation so that the construction design that will be used is safe.